Factors influencing work productivity among employees at the Aceh Provincial Health Office - Israknur, Israknur; Ginting, Johannes Bastira; Siregar, Santy Deasy (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Productivity is a critical measure of individual performance, particularly in the healthcare sector, where human resources play a pivotal role in achieving organisational and national development goals. This study examines the factors influencing work productivity among employees at the Aceh Provincial Health Office, focusing on education, motivation, discipline, work ethic, and work attitude. Using a descriptive quantitative approach with a cross-sectional design, data were collected from 100 employees through observation, interviews, and questionnaires. Univariate and bivariate analyses, including chi-square tests, were employed to assess the relationships between variables. The results indicate that 68% of employees demonstrated good work productivity. Motivation, discipline, work ethic, and work attitude showed statistically significant positive correlations with productivity (p = 0.000). Specifically, 95.2% of highly motivated employees exhibited good productivity, compared to only 25.2% of those with poor motivation. Similarly, 98.8% of disciplined employees and 81.5% of those with a strong work ethic demonstrated good productivity. A positive work attitude also correlated strongly with productivity (78.0% vs. 61.0% for negative attitudes). However, education level did not significantly influence productivity (p = 0.391), with 80% of highly educated and 66.7% of less educated employees showing good productivity. These findings highlight the importance of fostering motivation, discipline, work ethic, and positive work attitudes to enhance productivity in healthcare settings. While education level was not a significant factor, addressing the other variables can create a conducive work environment and improve service quality. This study underscores the need for organisations to prioritise these factors through incentives, recognition, and professional development opportunities to achieve optimal productivity and organisational success.